Analisis Kontekstual Hadis Tentang Wali Dan Kerelaan Perempuan dalam Pernikahan Terhadap Tradisi Kawin Lari (Merariq) Pada Masyarakat Lombok - Asep Hikmatullah; Nasrulloh (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This article aims to analyze hadiths concerning guardianship and women's consent in marriage and their relevance to the tradition of elopement (merariq) in Lombok society. Merariq is a traditional Sasak marriage practice that begins with the symbolic act of taking the bride before the formal marriage contract. In practice, this tradition often raises debates regarding the fulfillment of women's consent and the involvement of legal guardians as emphasized in the Prophet’s hadith. This study employs a library research method using a contextual analysis approach by examining hadith literature, classical commentaries, and socio-religious studies related to the merariq tradition. The findings indicate that hadiths concerning guardianship and consent emphasize the protection of women’s rights, the prevention of coercion, and the establishment of just marriage procedures. The merariq tradition can be aligned with Islamic legal values as long as it ensures genuine consent, legitimate guardian involvement, and the absence of coercion or harm. Therefore, contextual interpretation enables constructive integration between local cultural practices and Islamic normative principles.